(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
Quantas Marias existem? (How many Marias are there?) is a documentary on violence against women, which results from an amateur and collaborative production of movies. This paper describes the process of narrative construction, the visual meanings and subjective intersections. The objective is to map the movements and lines that make up this experience. It is an intervention-research that valued the participation of the women who were victims of violence in the script and production of the film. From the analyses, which mapped as movements and lines that made up the experience of making the documentary, the process of becoming a woman emerged as a common plan, forming a documentary-rhizome.